The iTRAPs: Guardians of Synaptic Vesicle Cargo Retrieval During Endocytosis - Gordon, Sarah L.; Cousin, Michael A. (Frontiers in Synaptic Neuroscience, 2016)
The reformation of synaptic vesicles during endocytosis is essential for the maintenance of neurotransmission in central nerve terminals. Newly formed synaptic vesicles must be generated with the correct protein cargo in the correct stoichiometry to be functional for exocytosis. Classical clathrin adaptor protein complexes play a key role in sorting and clustering synaptic vesicle cargo in this regard. However it is becoming increasingly apparent that additional “fail-safe” mechanisms exist to ensure the accurate retrieval of essential cargo molecules. For example, the monomeric adaptor proteins AP180/CALM and stonin-2 are required for the efficient retrieval of synaptobrevin II and synaptotagmin-1 respectively. Furthermore, recent studies have revealed that synaptobrevin II and synaptotagmin-1 interact with other synaptic vesicle cargoes to ensure a high fidelity of retrieval. These cargoes are synaptophysin (for synaptobrevin II) and SV2A (for synaptotagmin-1). In this review we summarise current knowledge regarding the retrieval mechanisms for both synaptobrevin II and synaptotagmin-1 during endocytosis. We also define and set criteria for a new functional group of synaptic vesicle molecules that facilitate the retrieval of their interaction partners. We have termed these molecules intrinsic trafficking partners (iTRAPs) and we discuss how the function of this group impacts on presynaptic performance in both health and disease.